2004
DOI: 10.1021/ol048610h
|View full text |Cite
|
Sign up to set email alerts
|

New Scavenger Resin for the Reversible Linking and Monoprotection of Functionalized Aromatic Aldehydes

Abstract: [reaction: see text] Polymer-supported benzylhydrazines were synthesized using poly(ethylene glycol) acrylamide (PEGA) resin. They can be used to scavenge electrophiles reactive with hydrazine. Especially aromatic aldehydes can be captured selectively, monoprotected, and reversibly linked in the presence of other functional groups, including electrophilic ones. Various reactions can be performed on these protectively linked aldehydes, which afterward can be released either with full restoration of the aldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…62 It has also been shown that aldehydes (and presumably ketones) immobilized via N-monoalkylhydrazone could be released from the polymeric support in the form of N,N-dialkylhydrazone via a hydrazone exchange reaction, i.e., treatment with a solution of N,Ndialkylhydrazine in the presence of concentrated hydrochloric acid (1-amino-4-methylpiperazine, 37% aqueous HCl/THF, 1:100). 310 Asymmetric alkylation of ketones or aldehydes is waiting to be widely implemented in SPAS. Proof of concept studies on the asymmetric (enantioselective) alkylation of ketones via supported chiral hydrazone auxiliaries have already been conducted independently by some research groups ( Figure 10).…”
Section: R-alkylation Of Polymer-supported Hydrazonesmentioning
confidence: 99%
“…62 It has also been shown that aldehydes (and presumably ketones) immobilized via N-monoalkylhydrazone could be released from the polymeric support in the form of N,N-dialkylhydrazone via a hydrazone exchange reaction, i.e., treatment with a solution of N,Ndialkylhydrazine in the presence of concentrated hydrochloric acid (1-amino-4-methylpiperazine, 37% aqueous HCl/THF, 1:100). 310 Asymmetric alkylation of ketones or aldehydes is waiting to be widely implemented in SPAS. Proof of concept studies on the asymmetric (enantioselective) alkylation of ketones via supported chiral hydrazone auxiliaries have already been conducted independently by some research groups ( Figure 10).…”
Section: R-alkylation Of Polymer-supported Hydrazonesmentioning
confidence: 99%
“…The synthesis is similar to that described in detail in ref. [8] Thus, PEGA 1900 and PEGA þ were reacted with benzaldehyde in the presence of trimethyl orthoformate for 24 h and room temperature to give 2a, b. Compound 2a, b was reduced with sodium triacetoxyborohydride in the presence of methanol/acetic acid (1% v/v) at room temperature for 48 h. After washing the resins 3a, b, they were reacted with di(bromomethyl)benzene and diisopropylethylamine in DMF for 48 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the use of PEGA resins (co-polymers of ethylene glycol and acrylamide) functionalised with hydrazides, as new scavenger for the reversible linking of aldehydes has been reported. [8] The same synthetic procedure was used for the synthesis of compound 5 on PEGA 1900 (5a) and PEGA þ (5b) (Scheme 2). PEGA þ , produced by Polymer Laboratories by introduction of charged monomers in the PEGA 1900 structure was demonstrated to improve PGA accessibility on the solid support due to electrostatic interactions.…”
Section: Abstract: Hydrazine; Hydrolysis; Penicillin G Amidase; Phenymentioning
confidence: 99%
See 1 more Smart Citation
“…A 60% yield of hydrolysis was reported for phenylacetic hydrazides anchored on the PEGA + polymer. This novel catalytic property was assayed on solid phase as a possible route to the design of ‘masked’ linkers, that upon selective cleavage can release the highly reactive hydrazine group 61. Upon hydrazide hydrolysis and release of the hydrazine function, an intramolecular nucleophilic attack would occur, leading to the release of the target molecule 60…”
Section: Application Of Solid Phase Biocatalysismentioning
confidence: 99%